Optical response of plasmonic nanostructures composed of coupled gold nanodisks. - Najah, S.; Jarmoumi, Y.; Akouibaa, A.; Fassi, S. El; Derouiche, A.; Ridouane, H. (IJRDO-Journal of Applied Science, 2016)
Due to the coupling effect of Surface Plasmon Resonance (SPR) excited by the incident electromagnetic wave, the gold nanodisks structures show special optical properties that can be applied in many fields of nano-technology. In this work, a model based on the finite element method (FEM) is developed to investigate the effect of the relevant parameters on the optical properties of gold nanodisks. The study is performed for various possible configurations, one, two, three and four gold nanodisks when they are aggregating in dielectric medium. Based on the accurate geometric parameters, we plotted the numerical results of the resonance energy in various conditions involving gap distance and radius of nanoparticles.